2016
DOI: 10.4103/0974-7796.184905
|View full text |Cite
|
Sign up to set email alerts
|

Is hemoglobin A1c level effective in predicting the prognosis of Fournier gangrene?

Abstract: Objectives:To evaluate the effect of immune failure and/or diabetes mellitus (DM) association on the mortality and morbidity of the Fournier's Gangrene (FG), and interrelatedly, the usability of HbA1c level in the prediction of prognosis.Materials and Methods:The data of 38 patients with the diagnosis of FG were investigated retrospectively. The patients were divided into two groups as patients with DM (Group 1, n = 18) and non-diabetics (Group 2, n = 20). The patients in group 1 were also divided into two sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…To address this, we included HbA1c levels as a laboratory test to predict diabetes-associated complications in DM patients. [ 24 ] Our findings indicate that high HbA1c levels (≥6.5) were significantly associated with mortality, in line with previous studies. [ 24 ] Elevated and uncontrolled blood glucose levels, as indicated by HbA1c, may lead to vascular disease and suppressed immunity, ultimately increasing susceptibility to mortality.…”
Section: Discussionsupporting
confidence: 92%
“…To address this, we included HbA1c levels as a laboratory test to predict diabetes-associated complications in DM patients. [ 24 ] Our findings indicate that high HbA1c levels (≥6.5) were significantly associated with mortality, in line with previous studies. [ 24 ] Elevated and uncontrolled blood glucose levels, as indicated by HbA1c, may lead to vascular disease and suppressed immunity, ultimately increasing susceptibility to mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Sen et al [14] indicate the need to determine glycated hemoglobin in order to predict the outcome of the disease, since patients with a high level of this indicator in the study had a significantly more often adverse outcome.…”
Section: Pathogenesismentioning
confidence: 99%
“…[ 12 ] In some studies, some diseases that cause an immune system failure (such as DM) have been reported to increase susceptibility to FG. [ 13 15 ] In the current study, 55.7% of the patients had one or more comorbid diseases. When evaluated concerning comorbidities, the most significant was seen to be DM in 43.4% of the current study patients, followed by other pathologies, namely chronic renal failure (CRF) and cardiac diseases.…”
Section: Discussionmentioning
confidence: 63%